The innovation of traditional handicrafts and cultural identity: A multidimensional value analysis using the DEMATEL-ISM method - Hong Li; Tao Xue; Zhong Zheng; Xuexing Luo; Guanghui Huang (PLoS ONE, 2025)
This study aims to explore how cultural identity influences the protection and innovation of traditional crafts through multidimensional pathways. Using the examples of macau shipbuilding and portuguese tile painting, 14 influencing factors were extracted from three dimensions—culture and expression, aesthetics and creation, and cognition and emotion—through the Delphi method and expert feedback. The decision-making trial and evaluation laboratory (DEMATEL) method was used to analyze causal relationships, and interpretive structural modelling (ISM) was employed to construct a hierarchical model consisting of core, direct, and indirect factors. The results indicate that historical continuity, knowledge transmission, and the integration of tradition and modernity are core factors, forming the cultural foundation for traditional craft innovation. Direct factors, such as creative expression, local culture, and emotional communication, play a pivotal role in connecting the core and indirect layers, while indirect factors like visual appeal, design originality, and craft education reflect the multidimensional value of traditional crafts. The study provides a clear, hierarchical pathway that explains the systematic process from cultural identity to innovation practice, offering valuable insights for sustainable craft innovation in the context of globalization.